Potential flows computer graphic solutions - Kirchhoff, Robert H. (Mechanical engineering (Marcel Dekker, Inc.), 1985)
Compiling 70 well-known potential flows in a unique, convenient format, this first-of-its-kind reference provides detailed computer graphic drawings in a nondimensional style that allows each solution to be scaled to any application.